Prenatal care in Southern Brazil: coverage, trend and disparities - Janaina S Saavedra; Juraci A Cesar; Angélica O Linhares (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To estimate coverage, examine trend and assess the disparity reduction regarding household income during prenatal care between mothers living in Rio Grande, state of Rio Grande do Sul, in 2007, 2010, 2013 and 2016. METHODS This study included all recent mothers living in this municipality, between 1/1 and 12/31 of those years, who had a child weighing more than 500 grams or 20 weeks of gestational age in one of the only two local maternity hospitals. Trained interviewers applied, still in the hospital and up to 48 hours after delivery, a unique and standardized questionnaire, seeking to investigate maternal demographic and reproductive characteristics, the socioeconomic conditions of the family and the assistance received during pregnancy and childbirth. To assess the adequacy of prenatal care, the criteria proposed by Takeda were used, which considers only the number of prenatal appointments and gestational age at initiation, and by Silveira et al., who in addition to these two variables, considers the achievement of some laboratory tests. Chi-square tests were used to compare proportions and assess the linear trend. RESULTS The total of 10,669 recent mothers were included in this survey (96.8% of the total). Prenatal coverage substantially increased between 2007 and 2016. According to Takeda, it rose from 69% to 80%, while for Silveira et al., it increased from 21% to 55%. This improvement occurred for all income groups (p < 0.01). The disparity between the extreme categories of income reduced, according to Takeda, and increased according to Silveira et al. CONCLUSIONS The provision of prenatal care, considering only the number of appointments and the early start, occurred in greater proportion among the poorest. However, only the richest recent mothers were contemplated with more elaborate care, such as laboratory tests, which increased the disparities in the provision of prenatal care.